Biosynthesis of the carbohydrate portions of immunoglobulin M - Parkhouse, R. M. E. (1971)
Incorporations of radioactive mannose, galactose and fucose into MOPC 104E mouse plasma-cell tumour suspensions suggest a stepwise addition of carbohydrate residues to immunoglobulin M (IgM) during the process of secretion. Mannose and glucosamine residues are added at an early stage, whereas galactose and fucose are added just before, or at the time that, IgM leaves the cell. Free light chains secreted in excess by the same tumour cells incubated with mannose, galactose or fucose contained barely detectable amounts of radioactivity.